Mothers' Economic Well-Being in Sole and Joint Physical Custody Families - Lara Augustijn (Journal of Family and Economic Issues, 2022)
Previous research has repeatedly shown that separation or divorce can lead to a substantial decline in economic resources, and that it is mostly mothers who suffer from the severe economic consequences. Because it has also been established that the post-separation care arrangement that a family practices is a central factor in explaining mothers' poor economic situations after family dissolution, this study investigated the association between physical custody arrangements (sole physical custody, asymmetric joint physical custody, and symmetric joint physical custody) and the economic well-being of 1018 residential mothers from the Family Models in Germany study. The results of the ordered logistic regression models showed that mothers in asymmetric and symmetric joint physical custody families reported higher levels of economic well-being than mothers with sole physical custody. When controlling for a set of confounders, the differences between mothers with sole physical custody and symmetric joint physical custody disappeared, which suggests that the economic advantages of mothers with symmetric joint physical custody can be fully explained by factors like the mothers' working hours, their personal net income, their partnership status, and the fairness of their financial arrangement with their former partner. In contrast, the relationship between asymmetric joint physical custody and mothers' economic situations remained significant even after control variables were included in the regression models. However, the question of what role selection processes among parents play in explaining the observed differences in post-separation economic well-being between mothers in sole and joint physical custody families remains open.
Keywords: 300; Asymmetric joint physical custody; Economic well-being; Family Models in Germany; Mothers; Sole physical custody; Symmetric joint physical custody